Engaging Efl Students in Reading Comprehension Through SQ3R Techniques: A Case Study - Septyawati, Karin; Setiasamsi, Yogi; Saefullah, Hilamnsyah (FKIP - Universitas Riau, 2025)
This study examines of the SQ3R (Survey, Question, Read, Recite, Review) technique in enhancing EFL students’ reading comprehension at vocational high schools and explores students’ responses to its implementation in reading activities. Employing a qualitative case study approach, the research involved 35 students as participants. Data were collected through observations and interviews, then analyzed using Braun & Clarke’s thematic analysis. The findings indicate that the SQ3R technique enhances student engagement in reading, facilitates deeper comprehension of texts, and strengthens critical thinking skills. Moreover, students became more systematic in processing information, which contributed to improved retention and understanding. However, some students faced challenges, particularly in formulating relevant questions and summarizing key points effectively. These difficulties highlight the need for additional guidance and practice. The study recommends integrating digital tools to support SQ3R implementation and providing targeted training sessions to help students maximize the benefits of this technique, ensuring more effective and independent reading comprehension development.